2005
DOI: 10.1111/j.1365-2966.2005.09111.x
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic microwave background temperature and polarization pseudo-Cestimators and covariances

Abstract: We develop the pseudo-C method for reconstructing the cosmic microwave background (CMB) temperature and polarization auto-and cross-power spectra, and estimate the pseudo-C covariance matrix for a realistic experiment on the cut sky. We calculate the full coupling equations for all six possible CMB power spectra, relating the observed pseudo-C values to the underlying all-sky C values, and test the reconstruction on both full-sky and cut-sky simulated CMB data sets. In particular we consider the reconstruction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
157
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(161 citation statements)
references
References 47 publications
(58 reference statements)
4
157
0
Order By: Relevance
“…For cut-sky, E(n) and B(n) mode decomposition is not unique [6,7]. But since mixing is linear there always exist two linearly independent modes.…”
Section: Cmb Anisotropy and Polarization Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…For cut-sky, E(n) and B(n) mode decomposition is not unique [6,7]. But since mixing is linear there always exist two linearly independent modes.…”
Section: Cmb Anisotropy and Polarization Mapsmentioning
confidence: 99%
“…In the latter case, the incomplete sky coverage immediately induces a contamination of E-mode of polarization by its B-mode and vice-versa. Then the modified temperature and polarization fields is related to their actual values of full sky coverage by a window matrix [6,7] whose elements are basically window functions for temperature and polarization in harmonic space. It can be shown that the estimated BipoSH coefficients are in fact linear combinations of that for fullsky CMB maps.…”
Section: Example: Polarized Synchrotron Contaminationmentioning
confidence: 99%
“…We estimate the recovered power spectra from the reconstructed shear and IA maps using the standard pseudo-C l approach (Brown & Battye 2011b;Hivon et al 2002;Brown et al 2005).…”
Section: Tests On Simulationsmentioning
confidence: 99%
“…Last maximum likelihood methods on CMB dataset were used in some parts of the Boomerang and Maxima datasets. Since N pix increased in the modern experiments, maximum likelihood methods are not a viable option and pseudo-C l methods [11][12][13] are used since then. We can explore the full posterior distribution with Monte Carlo sampling.…”
Section: Introductionmentioning
confidence: 99%